Penerapan Aplikasi Extraordinary CBT pada Penilaian Akhir Semester di MAN 3 Padang Pariaman - Edi Kurniawan; Nazarwin Nazarwin; Muhammad Kurniawan; Juliandri Hasnur; Miftahul Rizka; Yogi Yogi (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This community service program aims to enhance the skills of teachers and staff at MAN 3 Padang Pariaman in implementing the Extraordinary Computer Based Test (CBT) application for the final semester assessment. The main issue faced by the school was the manual paper-based test system, which was time-consuming, error-prone, and inefficient. Through a technical guidance (Bimtek) program, participants received theoretical and practical training on managing the CBT application, including question creation, participant data input, exam simulation, and automatic result processing. The activity was conducted over two days with 40 participants consisting of teachers and administrative staff. The evaluation results showed that 85% of participants strongly agreed that the application was easy to use, effective, and capable of improving exam efficiency. Furthermore, the implementation of this application increased students’ learning motivation and improved teachers’ professionalism in managing technology-based assessments. Therefore, this program successfully enhanced the participants’ digital competence and provided an innovative solution for the learning evaluation system at MAN 3 Padang Pariaman.